3D network modelling of fracture processes in fibre-reinforced geomaterials. (January 2019) - Grassl, Peter; Antonelli, Adrien
Abstract: The width of fracture process zones in geomaterials is commonly assumed to depend on the type of heterogeneity of the material. Still, very few techniques exist, which link the type of heterogeneity to the width of the fracture process zone. Here, fracture processes in geomaterials are numerically investigated with structural network approaches, whereby the heterogeneity in the form of large aggregates and low volume fibres is modelled geometrically as poly-dispersed ellipsoids and mono-dispersed line segments, respectively. The influence of aggregates, fibres and combinations of both on fracture processes in direct tensile tests of periodic cells is investigated. For all studied heterogeneities, the fracture process zone localises at the start of the softening regime into a rough fracture. For aggregates, the width of the fracture process zone is greater than for analyses without aggregates. Fibres also increase the initial width of the fracture process zone and, in addition, result in a widening of this zone due to fibre pull out.